Bertrand versus Cournot with Convex Variable Costs - Flavio Delbono; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
Within a simple model of homogeneous oligopoly, we show that the traditional ranking between Bertrand and Cournot equilibria may be reversed. For price setting entails a continuum of price equilibria under convex variable costs, departure from marginal cost pricing may be observed. As a consequence, Bertrand-Nash equilibrium profits (welfare) may be higher (lower) than Cournot-Nash ones. The reversal of the standard rankings occurs when pricing strategies mimic collusive behaviour.
Keywords: D43; L13; 330